Dining comfort in elderly care facility dining rooms and influencing factors before and after the outbreak of the COVID-19 pandemic - Mu, Jingyi; Kang, Jian (Frontiers in Psychology, 2023)
The COVID-19 pandemic has changed dining modes in elderly care facilities. This study explores the relationship between the dining environment of four elderly care facilities and the sensitivity of the elderly residents to it before and after the outbreak of the COVID-19 pandemic. The study examined differences in subjective comfort levels by measuring the facilities’ physical environment, analysing dining behaviour, and surveying the elderly residents. The findings are as follows. (1) The physical environmental parameters of the four dining rooms differed between the pre- and post-epidemic periods, as shown by increased Sound Pressure Level（SPL）, humidity, and temperature levels. (2) The residents’ evaluations of physical environment comfort also changed after the outbreak of the COVID-19 pandemic. The subjective comfort levels of the ‘dining with baffle’ and ‘dining across a seat’ modes decreased, though the level of the former was slightly higher than that of the latter. The elderly had stronger SPL tolerance in the dining with baffle mode and dining across a seat modes, and their subjective comfort levels for thermal environment and air quality were higher in the dining across a seat mode. (3) When dining time, crowd density, and communication frequency were kept equal, the subjective comfort level of the elderly in the dining with baffle mode and dining across a seat modes was lower than that in the ‘normal’ dining mode, when the level in the dining with baffle mode was lower than that in the dining across a seat mode. (4) Differences were observed in subjective comfort levels according to age, education level, and residence duration across the dining modes. For example, the higher the education level, the higher the acceptance of dining across a seat. Moreover, participants who had lived at the facility for three to five years gave the lowest evaluation in the dining with baffle mode.